Personal lies - Charness, Gary; Rodríguez-Lara, Ismael (Elsevier, 2023)
Using the mind game, we provide experimental evidence that people are more likely to lie when they disclose non-personal information (e.g., reporting a number they thought of) compared with personal information (e.g., reporting the last digit of their birth year). Our findings suggest that the type of information is an important factor for lying behavior.
Keywords: Verdad y mentira; Autopercepción; Creencias; Lying behavior; Personal information; Impersonal information; Self-concept-maintenance; Moral costs; Motivated beliefs